2012
DOI: 10.1002/cbdv.201100142
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitane Triterpenoids from the Leaves of Momordica charantia, and Their Cancer Chemopreventive Effects and Cytotoxicities

Abstract: Seventeen cucurbitane-type triterpenoids, 1-17, including six new compounds, (23E)-3β,25-dihydroxy-7β-methoxycucurbita-5,23-dien-19-al (1), (23S*)-3β-hydroxy-7β,23-dimethoxycucurbita-5,24-dien-19-al (6), (23R*)-23-O-methylmomordicine IV (7), (25ξ)-26-hydroxymomordicoside L (8), 25-oxo-27-normomordicoside L (9), and 25-O-methylkaravilagenin D (12), were isolated from a MeOH extract of the leaves of Japanese Momordica charantia. The structures of new compounds were elucidated on the basis of extensive spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…In addition, leaves also considered as important sources of triterpenoids. Zhang et al [35] isolated seventeen cucurbitane-type triterpenoids with six new compounds (23E)-3β,25-dihydroxy-7 β-methoxycucurbita-5, In addition, two new charantin group triterpenoids charantin A and charantin B were recently isolated from the leaves of M. charantia [36]. A number of non-specific measures of saponin derivatives also exist in Momordica species.…”
Section: Cucurbitane Type Triterpenoidsmentioning
confidence: 95%
“…In addition, leaves also considered as important sources of triterpenoids. Zhang et al [35] isolated seventeen cucurbitane-type triterpenoids with six new compounds (23E)-3β,25-dihydroxy-7 β-methoxycucurbita-5, In addition, two new charantin group triterpenoids charantin A and charantin B were recently isolated from the leaves of M. charantia [36]. A number of non-specific measures of saponin derivatives also exist in Momordica species.…”
Section: Cucurbitane Type Triterpenoidsmentioning
confidence: 95%
“…Historically, all parts of the bitter melon plant, from the roots to fruit to seeds, have been used to ameliorate various health conditions; hence, several studies have isolated and characterized CTMs from different parts of the plant. In most previously published reports, extraction of these molecules from plant material was usually carried out using alcohol or an aqueous/alcoholic mixture (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The extractions were typically performed at room temperature on a mechanical shaker for a period of a day to several weeks (31)(32)(33).…”
Section: A Solvent Extractionsmentioning
confidence: 99%
“…Another commonly-reported resin used for the separation of CTMs is Sephadex LH-20 (33,44,45). After an initial purification through silica, the resulting extracts were then subjected to various chromatographic techniques using LH-20 and other resins, but principally silica gel (23,25,26,34). Fractions collected from the various chromatographic runs were further separated by high-performance liquid chromatography (HPLC) and molecules were identified based on ultraviolet (UV), infrared (IR), nuclear magnetic resonance (NMR), and mass spectrometry (MS) to elucidate their structures (22,23,27,29).…”
Section: A Open Column Chromatographymentioning
confidence: 99%
“…In the course of our research for bioactive secondary metabolites from Taiwanese M. charantia, we had reported the isolation and structure elucidation of twenty-five cucurbitanetype triterpenoids from the MeOH extract of the stems of this plant. [21][22][23][24][25] In the continuing phytochemical investigation on M. charantia, we further identified two new cucurbitane-type triterpenoids, 25-methoxycucurbita-5,23(E)-diene-3b,19-diol (1) and 7b-ethoxy-3b-hydroxy-25-methoxycucurbita-5,23(E)-dien-19-al (2), together with three known triterpenes, 3b,7b,25-trihydroxycucurbita-5,23(E)-dien-19-al (3), 11,26 (23E)-3b-hydroxy-7b,25-dimethoxycucurbita-5,23-dien-19-al (4), 6 and 3b-hydroxy-25-methoxycucurbita-6,23(E)-dien-19,5b-olide (5), 20 from the fruit pulp of M. charantia ( Figure 1). In this paper, we reported the isolation, structure elucidation and cytotoxic activity of compounds 1-5.…”
Section: Introductionmentioning
confidence: 99%
“…Tissues of this plant have been used not only as a vegetable, but also as a folk medicine for the treatment of diabetes and bitter stomachic in Asian. Several pharmacological investigations have showed that the extracts or compounds of tissues of M. charantia possess cytotoxic, anti-diabetic, and anti-inflammatory activities [1][2][3][4] More than seventy cucurbitane-type triterpenes have been isolated from the fruits, [3][4][5][6][7][8][9][10][11][12][13][14] seeds, 15,16 root, 17 leaves and vines [18][19][20] of M. charantia. In the course of our research for bioactive secondary metabolites from Taiwanese M. charantia, we had reported the isolation and structure elucidation of twenty-five cucurbitanetype triterpenoids from the MeOH extract of the stems of this plant.…”
Section: Introductionmentioning
confidence: 99%